The potential of using plant-growth-stimulating bacteria in phytoremediation of coal dumps - Borodina Ekaterina; Asyakina Lyudmila; Proskuryakova Larisa; Osintseva Maria; Milentyeva Irina; Prosekov Aleksandr (BIO Web of Conferences, 2024)
The process of phytoremediation holds great promise for repairing soils damaged by coal mining. Due to the extreme conditions typical of coal dumps, plants face undesirable consequences, which inevitably entail a decrease in the effectiveness of soil restoration. Research in the area of enhancing plant survival has demonstrated that the use of plant growth-promoting microorganisms can be effective. These microorganisms must exhibit resistance to heavy metals in order to sustain their viability in polluted soils. The objective of this investigation was to identify growth-stimulating microorganisms that exhibit resistance to heavy metals and to examine their impact on plants under laboratory conditions. The investigation yielded the identification of 11 isolates from technogenic soils in the Kuzbass region. One of the strains demonstrated a low resistance to copper, zinc, iron, and manganese, thus excluding it from further investigation. The remaining 10 strains were examined for their growth-stimulating properties, including gibberellic acid, indole-3-acetic acid, kinetin, cytokinin, and antioxidant activity. Based on the results of biological compatibility testing, two consortium variants were formed from the five most promising isolates. The utilization of these consortiums for the treatment of coal mine waste soils resulted in a higher survival rate of the grass mixture under laboratory conditions. Consortium № 1, which had isolates 1, 4, and 6 in a ratio of 1:1:1 at a concentration of 1:50, was the most effective. The microorganisms that were included in this consortium were identified based on their cultural, morphological, and biochemical characteristics as Enterobacter cloacae, Acinetobacter geminorum, and Lelliottia amnigena. The strains obtained in this study have the potential to restore vegetation and soil fertility in coal mine waste areas. Further research will be conducted to investigate the impact of these strains on the accumulation of heavy metals. The consortium and the biopreparation developed on its basis will be examined under field conditions.